ADAPTATION OF THE TERMINOLOGY OF BUILDING MATERIALS TO INTERNATIONAL STANDARDS: ANALYSIS IN RUSSIAN, UZBEK AND ENGLISH - Madina Nosirovna Musurmankulova (Research Focus International Scientific Journal, 2025)
this article covers the process of adaptation of the terminology of building materials to international standards in Russian, Uzbek and English on the basis of linguistic, semantic and comparative analysis. The peculiarities in the trilingual use of terms related to building materials, their compatibility with international standards, as well as the problems encountered in the translation process are analyzed on a scientific basis. The study also includes practical recommendations on the adaptation of local terms to internationally accepted forms. This article can serve as a scientific resource in the development of International Communication and standardization of terms in the field of building materials.